Thermokeratoplasty for treatment of indolent corneal ulcer of endothelial origin in the dog. Report of two cases - LIAPIS (Ι. Κ. ΛΙΑΠΗΣ), C. I. (Journal of the Hellenic Veterinary Medical Society, 2017)
Two cases of endothelial degeneration and indolent corneal ulcer are reported. In the first case, a 14-year-old, female Dalmatian dog had a 1-year history of endothelial degeneration and an indolent corneal ulcer of 2 months duration. In the second case a 10-year-old, male Springer spaniel dog, had a 6 months history of endothelial degeneration and an indolent corneal ulcer of 1 month duration. In both cases medical and surgical treatment had failed. Thermokeratoplasty was performed in both cases, followed by soft contact lens application and administration of topical antibiotics and mydriatics/cycloplegics. The healing time was 4 and 5 weeks respectively. In both cases the result was in accordance with the previously reported cases confirming that thermokeratoplasty is the treatment of choice in case of indolent corneal ulcer of endothelial origin.